Executing Hadhanah Decisions in Indonesia’s Religious Courts: Islamic Legal Principles, Child Welfare, and Multicultural Challenges - Putri, Viorizza Suciani; Chami, Yassine (Kawanua International Journal of Multicultural Studies, 2025)
This article examines the execution of hadhanah (child custody) decisions in Indonesia’s Religious Courts, focusing on the interaction between Islamic legal principles, child welfare considerations, and multicultural social realities. Using a normative-qualitative approach, the study analyzes statutory regulations, judicial decisions, and relevant Islamic legal doctrines to identify challenges in implementing hadhanah rulings after divorce. The findings reveal that although Religious Courts consistently prioritize the principle of the best interests of the child, the execution of custody decisions often encounters obstacles, including parental resistance, socio-cultural norms, and limited enforcement mechanisms. Multicultural contexts—such as differing religious interpretations, family structures, and local customs—further complicate the effective realization of judicial decisions. The study argues that the gap between normative legal ideals and practical enforcement undermines child protection and legal certainty. It proposes strengthening judicial discretion, enhancing mediation mechanisms, and integrating child-centered and culturally sensitive approaches into hadhanah execution. This article contributes to the discourse on Islamic family law by highlighting the need for a more responsive and welfare-oriented framework in implementing custody decisions within Indonesia’s plural legal and social landscape